Pengaruh Brand Image dan Brand Trust Terhadap Brand Loyalty Produk Hand & Body Lotion Citra (Studi Pada Followers Akun Shopee Unilever Beauty Shop) - Laila Romadhoni Ayu Fitria; Ety Dwi Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine and analyze the influence of brand image and brand trust on brand loyalty of Citra hand & body lotion products (Study on followers of the Unilever Beauty Shop shopee account). This research uses a quantitative type of research. Variable measurement in this research uses a Likert scale. The population in this study are followers of the Unilever Beauty Shop Shopee account. The sample taken in this research was 100 people using purposive sampling technique. Data collection in this research used a questionnaire. This research uses SPSS for Windows version 29. The results of the research show that Brand Image and Brand Trust have a significant effect on Brand Loyalty, Brand Image has a significant effect on Brand Loyalty and Brand Trust has a significant effect on Brand Loyalty.